Information Literacy, fake news and disinformation: research analysis in the Brazilian context - Ancanello, Juliana Venancio [UNESP]; Casarin, Helen de Castro Silva [UNESP]; Furnival, Ariadne Chloe (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2023)
This study analyzes the main approaches and authors of publications about Information Literacy related to fake news and disinformation indexed in the databases Base de Dados Referenciais de Artigos de Periodicos em Ciencia da Informacao, Biblioteca Digital Brasileira de Teses e Dissertacoes and Catalogo de Teses e Dissertacoes CAPES until 2021. The corpus of analysis consisted of 32 items. The study demonstrates a growing trend in the number of publications from 2018 onwards. As for the content, the publications were grouped into seven categories and the category with the largest number of studies includes papers about information and health in the context of fake news and disinformation related to information literacy. It was shown that the complexity regarding the different approaches to information literacy related to the equally complex phenomenon of disinformation and fake news reveals that it is an emerging study theme in the area, guaranteed through theoretical studies and applied to different groups, to mitigate the effects of fake news and disinformation.
Keywords: Information Literacy; fake news; disinformation; scientific production